Hungary. - Phillips, Adrian, ....-; Scotchmer, Jo, ....- (Chalfont St Peter : Bradt Travel Guides, 2010)
With numerous air and rail links, keen foreign interest in the local property market, a solid spot in the world's top-10 conference destinations for business, and significant recent investment in hotels, spas and other facilities, Hungary's tourist industry is booming. The first edition of Bradt's Hungary was voted Best Guide Book of the Year by the British Guild of Travel Writers; this thoroughly updated second edition further strengthens the guide, offering expanded coverage of the resort-destination of Lake Balaton (which now has its own airport), new walking trails in the countryside, details of the best thermal baths, information on dental and medical tourism, and much more.
Keywords: Hongarije -- Reisgidsen